Prevention of perinatal group B streptococcal infections - (:unkn) unknown (My University, 1998)
Group B streptococcus is a leading cause of serious neonatal infections, such as congenital pneumonia, sepsis or meningitis. In pregnant women the infections due to group B streptococcus include urinary tract infection, chorioamnionitis, endometritis and less frequently pelvic thrombophlebitis or endocarditis. Intrapartum antimicrobial prophylaxis to women who are at increased risk for transmitting the infection to their newborns is an effective prevention method. Despite its effectiveness it has not been implemented widely or consistently. Center for disease control recommends use of one of two prevention strategies. In the first strategy, intrapartum antimicrobial prophylaxis is given to all women colonized with group B streptococcus or who develop premature onset of labor, prolonged rupture of membranes or intrapartum fever. In the second strategy, intrapartum antimicrobial prophylaxis is provided to women who develop obstetric risk conditions without prenatal group B streptococcus screening culture. A coordinated approach among obstetricians and pediatricians is needed to reduce the incidence of perinatal group B streptococcal infections.
Keywords: Group B streptococcus; Intrapartum antimicrobial prophylaxis; Perinatal infections